Yield and economic analysis of soybean cultivation in succession with different autumn/winter crops in Midwest of Paraná, Brazil - Soares Wenneck, Gustavo; Saath, Reni; Soares Wenneck, Guilherme; Villa e Vila, Vinicius; Rezende, Roberto; Ghuidotti, Gabriela Cristina (Revista Ceres, 2023)
Soybean and corn succession system widely adopt in different agricultural regions from Brazil. However, different species incorporation, especially in the autumn/winter season, can influence the soybeans profitability in succession system and farm economic return, providing benefits for the agricultural sector. The objective this work was to analyze the development of different species in the autumn-winter crop and the influence on soybean yield and the economic return of farm in Midwest of Paraná, Brazil. The study was conducted during 2019/2020 and 2020/2021 crop. A completely randomized design adopted, with eight treatments (autumn/winter season) and four replications. In autumn/winter season were composed of five crops in single system (black oat, brachiaria ruziziensis, oilseed radish, corn and wheat), two in intercropped systems (black oat with oilseed radish and corn with brachiaria) and fallow area (spontaneous plants). In the spring/summer season, soybean was cultivated. The biomass produced in the autumn/winter season varies with the species and cultivation system adopted. Soybean yield is higher when cultivated in succession to brachiaria, while the worst performance is obtained in succession to spontaneous plants. The cultivation of wheat in the winter and soybeans in the summer presents superior economic performance.